2021
DOI: 10.3390/microorganisms9081741
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Insights into Drug Resistance Determinants in Cedecea neteri, A Rare Opportunistic Pathogen

Abstract: Cedecea, a genus in the Enterobacteriaceae family, includes several opportunistic pathogens reported to cause an array of sporadic acute infections, most notably of the lung and bloodstream. One species, Cedecea neteri, is associated with cases of bacteremia in immunocompromised hosts and has documented resistance to different antibiotics, including β-lactams and colistin. Despite the potential to inflict serious infections, knowledge about drug resistance determinants in Cedecea is limited. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…These characteristic bacteria are significantly positively correlated with geniposidic acid. Cedecea has been found in the endophytic bacteria of medicinal plants such as Rosmarinus officinalis and Aloe vera (Akinsanya et al, 2015 ; Sharma et al, 2021 ; Ryan et al, 2022 ; Wang et al, 2023 ), but most reports on Cedecea have focused on its clinical pathogenicity (Ramaswamy et al, 2019 ; Thompson and Sharkady, 2021 ). Sphingobacterium is a gram-negative bacterium with wide distribution and strong stress resistance, and rarely causes human infection (Cai et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These characteristic bacteria are significantly positively correlated with geniposidic acid. Cedecea has been found in the endophytic bacteria of medicinal plants such as Rosmarinus officinalis and Aloe vera (Akinsanya et al, 2015 ; Sharma et al, 2021 ; Ryan et al, 2022 ; Wang et al, 2023 ), but most reports on Cedecea have focused on its clinical pathogenicity (Ramaswamy et al, 2019 ; Thompson and Sharkady, 2021 ). Sphingobacterium is a gram-negative bacterium with wide distribution and strong stress resistance, and rarely causes human infection (Cai et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical strains of Cedecea species exhibit natural resistance to various antimicrobial agents such β-lactams and colistin, which tend to confer the behavior of an emerging opportunistic human pathogen (Thompson and Sharkady 2021). Studies have reported that Cedecea encodes genes for antimicrobial resistance, but the exact proteins encoding such genes are not known (Thompson and Sharkady 2021;Notter et al 2022;Ginn et al 2018) In 2015, a previously undiscovered species from the genus Cedecea, specifically identified as Cedecea neteri SSMD04, was first isolated from pickled mackerel sashimi (Tan et al 2015). C. neteri SSMD04 is a gram-negative, bacillus that is found relatively rare in nature, but was recently identified as the infectious agent of a urinary tract infection in a pregnant female with polyhydramnios (Ahmad et al 2021).…”
Section: Introductionmentioning
confidence: 99%